Analyzing and simulating fracture patterns of Theran wall paintings - Shin, Hijung; Doumas, Christos; Funkhouser, Thomas; Rusinkiewicz, Szymon; Steiglitz, Kenneth; Vlachopoulos, Andreas; Weyrich, Tim (Journal of Computing and Cultural Heritage, 2012)
In this article, we analyze the fracture patterns observed in wall paintings excavated at Akrotiri, a Bronze Age Aegean settlement destroyed by a volcano on the Greek island of Thera around 1630 BC. We use interactive programs to trace detailed fragment boundaries in images of manually reconstructed wall paintings. Then, we use geometric analysis algorithms to study the shapes and contacts of those fragment boundaries, producing statistical distributions of lengths, angles, areas, and adjacencies found in assembled paintings. The result is a statistical model that suggests a hierarchical fracture pattern where fragments break into two pieces recursively along cracks nearly orthogonal to previous ones. This model is tested by comparing it with simulation results of a hierarchical fracture process. The model could be useful for predicting fracture patterns of other wall paintings and/or for guiding future computer-assisted reconstruction algorithms. © 2012 ACM.
CRIS-Team Scopus Importer:2022-07-26
Keywords: Cultural heritage; Hierarchical fracture; Statistical modeling